The effect of landmarks on visitors' attachment towards the historic city of Banda Hilir, Melaka - Mirsa Hussain, Khairul Amin; Ujang, Norsidah; Mohd Ali, Noor Azizi (Sustainable Tourism Research Cluster, Universiti Sains Malaysia, 2013)
Landmarks are strongly associated with tourism activities as they are regarded as the main attraction of a city. Due to the increase in new development, the attraction of landmarks is diluted. A similar threat is observed in Banda Hilir, Melaka, whereby new commercial buildings have dominated the overall structure of the historic city. As a result, its sense of place is diminishing, which may affect the visitors’ sense of attachment and belonging. This paper discusses the visitors’ attachment to the landmarks in Banda Hilir. Face-to-face interviews are conducted with visitors to understand their sense of attachment to the landmarks identified in the study. The results indicate that the visitors’ attachment differs and is influenced by the physical characteristics of the historical landmarks, the length of engagement and familiarity with the places. They are more attached to landmarks with dominating physical appearance that make them more memorable. The findings indicate the importance of visitors’ attachment in enhancing the attraction of landmarks within tourism attraction sites and as a guide when managing the redevelopment project for a historic town or city.